2019
DOI: 10.3390/ma12213594
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Shear Deformation on Permeability of 2.5D Woven Preform

Abstract: The accurate prediction of the permeability is the key to optimizing the molding process of fiber reinforced composites, thus to improve the composite quality, and reduce the material and labor costs in the manufacturing process. In this paper, the permeability of 2.5D woven preform with shear deformation was studied by experiments and numerical simulations. The permeabilities of the samples under various shear angles were measured by the radial flow method. An RVE (representative volume element) model based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The first cause, change of fibre volume fraction, is much stronger than the second. A simplified estimation of the preform permeability after shear can be done using Kozeny-Carman-type equation with the constants evaluated based on the non-sheared configuration [247][248][249]. Apart from the change of principal values, the rotation of the permeability must be considered [250].…”
Section: Permeabilitymentioning
confidence: 99%
“…The first cause, change of fibre volume fraction, is much stronger than the second. A simplified estimation of the preform permeability after shear can be done using Kozeny-Carman-type equation with the constants evaluated based on the non-sheared configuration [247][248][249]. Apart from the change of principal values, the rotation of the permeability must be considered [250].…”
Section: Permeabilitymentioning
confidence: 99%
“…Thanks to good film-forming properties, low cost, biocompatibility and biodegradability, fish gelatin has been recently recommended for the preparation of biodegradable films in active food packaging, replacing conventional non-biodegradable polymers and other mammalian-based gelatins [ 149 , 150 ]. Gelatin is easily processed by applying heat and mechanical stress in extrusion-based technologies [ 53 ].…”
Section: Applications In Food Packagingmentioning
confidence: 99%
“…They are tasteless, colorless, transparent, water-soluble and present higher flexibility properties than other bio-based films for food packaging [ 149 ]. Since the melting point of gelatin is close to body temperature, the gelatin-based films can be used for the preparation of edible films [ 132 , 150 ]. In addition, fish gelatin has shown great potential as an excellent matrix to host bio-active compounds with enhanced functionalities, such as antioxidant/antimicrobial [ 149 ].…”
Section: Applications In Food Packagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, a multi-layer fiber preform is used, composed of several different layers whose orientation and stacking sequence should optimize the mechanical performance. Different measurement methods are available in the literature, mostly related to the in-plane permeability, but there is not yet a standard procedure [27,28] and the data, obtained using different methods and different fabric architecture, are often not consistent [29]. Very few studies are reported on out-of-plane permeability, which is more difficult to measure [30,31].…”
Section: Introductionmentioning
confidence: 99%